A rodent model of intra-amniotic inflammation/infection, induced by the administration of inflammatory agent in a gestational sac, associated with preterm delivery: a systematic review. (18th April 2022) - Stranik, Jaroslav; Kacerovsky, Marian; Vescicik, Peter; Faist, Tomas; Jacobsson, Bo; Musilova, Ivana
Abstract: Background: Rodents are the most commonly used animals in the study of spontaneous preterm delivery (PTD). Intra-amniotic inflammation/infection is a frequent and important cause of PTD. Intraperitoneal and intrauterine administrations of inflammatory agents are traditional methods to establish a rodent model of PTD associated with inflammation and infection. The intra-amniotic administration of inflammatory or infectious triggering agents to rodents can be useful to study not only intra-amniotic inflammatory response but also PTD associated with intra-amniotic inflammation/infection. Objective: This systematic review aimed mainly to assess and analyze all described methods of intra-amniotic administration of infectious and/or inflammatory agents to create a rodent model of intra-amniotic inflammation associated with PTD. Methods: A literature search through two electronic databases from their earliest entries to February 2019 was performed. The selection criteria were as follows: (1) rodents as model animals, (2) a model of intra-amniotic inflammation/infection associated with PTD, and (3) intra-amniotic administration of triggering agents. Data extraction included specification of the study (author and year of publication), characteristics of study animals (species, strain, and number of animals), characteristics of intervention (timing and used technique), substance used for induction of intra-amniotic inflammation/infection, and outcome assessment. Results: The search identified a total of 4673 articles, of which 118 were selected for full-text reading, but only 13 studies were included in the review. Intra-amniotic administration was used only in the articles that were published beyond 2004. Two different approaches were identified: (1) open surgery with direct puncture of the amniotic sacs and (2) transabdominal ultrasound-guided puncture of the gestational sacs. Live microorganisms ( Ureaplasma parvum ), bacterial products (extracellular membrane vesicles), and pathogen-associated (lipopolysaccharide) and damage-associated molecular patterns (high mobility group box-1, S100B, and surfactant protein A) were used to simulate intra-amniotic inflammation/infection. Differences in the effect on intra-amniotic inflammation/infection associated with PTD in the mouse model were identified among triggering agents. Intra-amniotic application of lipopolysaccharide in the rat model caused intra-amniotic inflammation, but it did not lead to PTD. Conclusion: The intra-amniotic administration of the triggering agents can be used to study intra-amniotic inflammatory response and intra-amniotic inflammation/infection in the rodents model.